Xavier Ribas : un divertissement idéal - Ribas, Xavier (CV Photo, 2000)
Summary Our leisure activities are less and less distinguishable from models of productivity. Organized leisure has tentacles. It is probably to escape this logic that people meet spontaneously in less domesticated urban zones to partake freely of activities of relaxation.